Rezolucje interpretacyjne Rady Nieustającej - Głuszak, Marcin (Czasopismo Prawno-Historyczne, 2018)
One of the most important powers of the Permanent Council that functioned in the years 1775 1789 in Poland was the interpretation of the law in force. The Council issued interpretative resolutions based on the drafts prepared by the Department of Justice, and those resolutions were subsequently approved at the Council’s plenary sessions. Minutes of the Permanent Council’s sessions that have been preserved to these days were the subject of a study which subsequently allowed to identify the entities which petitioned for the interpretation of an unclear provision, the main reasons of doubts in the construction of law, and the main issues or problems that needed to be clarifi ed. The knowledge gained from this study sheds new light on the performance of the Permanent Council which was the fi rst central body of executive power operating in the Polish territory.